Genetic and physical mapping of the earliness perse locus Eps - Am1 in Triticum monococcum identifies early flowering 3 (ELF3) as a candidate gene - Tranquilli, Gabriela (2016)
Wheat cultivars exposed to optimal photoperiod and vernalization treatments still exhibit differences in heading time. This variation, known as earliness per se (Eps), is important for the fine-tuning of flowering and the adaptation to different environments. We previously identified the Eps-Am1 locus from Triticum monococcum and showed that the allele from cultivated accession DV92 significantly delays flowering and increases the number of spikelets per spike relative to the allele from wild accession G3116. We expanded a high-density genetic map and physical map of the Eps-Am1 region and identified the wheat ortholog of circadian clock regulator EARLY FLOWERING 3 (ELF3) as one of the candidate genes. No differences were found in ELF3 transcript levels between NILs carrying the DV92 and G3116 Eps-Am1 alleles, but the encoded ELF3 proteins differed in four amino acids. These differences were associated with altered transcription profiles of PIF-like, PPD1 and FT1, which are known downstream targets of ELF3. Tetraploid wheat lines with combined truncation mutations in the A- and B-genome copies of ELF3 flowered earlier and had less spikelets per spike than the wild type control under SD and LD conditions. Both effects were stronger in the photoperiod sensitive than the photoperiod insensitive background, indicating an epistatic interaction between PPD1 and ELF3. By contrast, the introgression of the T. monococcum chromosome segment carrying Eps-Am1-l allele from DV92 into durum wheat delayed flowering and increased the number of spikelets per spike in the field, providing a novel allele to modulate flowering time and spike development in wheat.